Racial discrimination and allostatic load among First Nations Australians: a nationally representative cross-sectional study - Leah Cave; Matthew N. Cooper; Stephen R. Zubrick; Carrington C. J. Shepherd (BMC Public Health, 2020)
Abstract Background Increased allostatic load is linked with racial discrimination exposure, providing a mechanism for the biological embedding of racism as a psychosocial stressor. We undertook an examination of how racial discrimination interacts with socioecological, environmental, and health conditions to affect multisystem dysregulation in a First Nations population. Methods We conducted latent class analysis (LCA) using indicators of life stress, socioeconomic background, and physical and mental health from a nationally representative sample of Australian Aboriginal adults (N = 2056). We used LCA with distal outcomes to estimate the effect of the latent class variable on our derived allostatic load index and conducted a stratified analysis to test whether allostatic load varied based on exposure to racial discrimination across latent classes. Results Our psychosocial, environmental, and health measures informed a four-class structure; ‘Low risk’, ‘Challenged but healthy’, ‘Mental health risk’ and ‘Multiple challenges’. Mean allostatic load was highest in ‘Multiple challenges’ compared to all other classes, both in those exposed (4.5; 95% CI: 3.9, 5.0) and not exposed (3.9; 95% CI: 3.7, 4.2) to racial discrimination. Allostatic load was significantly higher for those with exposure to racial discrimination in the ‘Multiple challenges’ class (t = 1.74, p = .04) and significantly lower in the ‘Mental health risk’ class (t = − 1.67, p = .05). Conclusions Racial discrimination may not always modify physiological vulnerability to disease. Social and economic contexts must be considered when addressing the impact of racism, with a focus on individuals and sub-populations experiencing co-occurring life challenges.